Value creation framework for multi-channel services in banking industry - Manochehr Zamani Farizhandi; Payam Hanafizadeh; Zohreh Dehdashti Shahrokh (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2019)
Nowadays, banking industry analogous with another industries has been encountered with digital transformation. Such transformation stemmed from convergence technologies. The underpinning point of convergency in such technologies is employing multi-channel services in order to delightful and remarkable customer experience. Based on the importance of customer experience, multi-channel services in banking industry has assumed significance attention among banking practitioners and scholars. Consequently, delivering services through different, aligned and complementary channels pointed as strategic requirement in banking industry. Accordingly, this study seeks to develop a framework for value creation for multi-channel services in banking. To accomplish such an objective, utilizing content analysis technique, 47 articles published in the realm of multi-channel services in banking in the period 2004 to 2019 considered and assessed. The findings suggest that a value creation framework for multi-channel services in banking must consider different factors such as: beliefs about intelligent financial behaviors, customer enablers, intelligent norms, intelligent tasks and intelligent technologies.